Analisis Manajemen Pemberdayaan Ekonomi Masyarakat Melalui Program Zakat Produktif di Baznas Kota Jambi - -, Suhardi; Majid, Nazori; -, Rafidah (Indonesian Journal of Islamic Economics and Business, 2024)
This research aims to find out what efforts are being made by BAZNAS Jambi City to manage productive zakat empowerment in improving the community's economy, find out what programs are distributed and to find out what are the causes of obstacles and supporters of mustahik's success in empowering productive zakat. This research uses qualitative methods, the data sources used are primary and secondary data sources with data collection techniques and instruments through interviews and documentation. The research results show that BAZNAS Jambi City has carried out management functions in managing zakat. The planning process involves determining the program and the amount of funds distributed to each BAZNAS program. The implementation of the organizing function can be seen in the BAZNAS organizational structure which describes the grouping of activities. However, the management function is still not optimal in terms of implementation and supervision due to several obstacles, namely limited professional human resources in managing zakat and lack of monitoring by BAZNAS towards zakat recipients. The flagship program from BAZNAS can provide positive value for economic empowerment and the direct impact of productive zakat is mustahik income. Efforts have been made to improve the management and empowerment of zakat in the city of Jambi, although it is still not optimal and effective, but BAZNAS continues to try to improve its performance and increase the professionalism of Human Resources at the BAZNAS Institution and continue to collaborate with related parties to support the implementation of the goals of BAZNAS.